2016
DOI: 10.1186/s12910-016-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of patient perspectives on the research use of health information and biospecimens

Abstract: BackgroundPersonal health information and biospecimens are valuable research resources essential for the advancement of medicine and protected by national standards and provincial statutes. Research ethics and privacy standards attempt to balance individual interests with societal interests. However these standards may not reflect public opinion or preferences. The purpose of this study was to assess the opinions and preferences of patients with kidney disease about the use of their health information and bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…31 Although we could not calculate the recruitment/participation rate for the current survey, we suspect that many potential respondents, especially those who found the survey through social media, reviewed the consent page and perceived the survey as too long or too formal. As such, although we intended to recruit a larger, more generalizable sample than those in prior Canadian investigations that limited sampling to patients with specific diagnoses (182-235 respondents each), [17][18][19] our findings cannot be generalized to the entire Canadian population and must be interpreted cautiously.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Although we could not calculate the recruitment/participation rate for the current survey, we suspect that many potential respondents, especially those who found the survey through social media, reviewed the consent page and perceived the survey as too long or too formal. As such, although we intended to recruit a larger, more generalizable sample than those in prior Canadian investigations that limited sampling to patients with specific diagnoses (182-235 respondents each), [17][18][19] our findings cannot be generalized to the entire Canadian population and must be interpreted cautiously.…”
Section: Limitationsmentioning
confidence: 99%
“…Prior Canadian studies focused on a single issue (namely, consent preferences for research use of medical records) [14][15][16] or sampled patients with specific diagnoses. [17][18][19] In the present study, researchers and patient leaders from 3 national joint and skin disease organizations developed and distributed an online survey to benchmark the views of Canadians about the use of large sets of routinely collected data in health research.…”
mentioning
confidence: 99%
“…Studies have shown that patients and their representatives, when given adequate information, are largely in favour of biomaterials not required for diagnostic procedures being made available for research projects. 71,72 However, important ethical, legal, privacy, and practical aspects relating to the collection, storage, shipment, and sharing of biomaterials need careful consideration (panel 2). For example, the legal definition of ownership of biomaterials and the guidelines for informed consent might vary between countries, 73 and should be considered in the context of individual patient care and international clinical trials.…”
Section: Ethical Legal Privacy and Practical Aspectsmentioning
confidence: 99%
“…EHR privacy concerns have been confirmed even among subjects who agree that EHRs are more efficient than paper records [17] and are not necessarily limited to individuals who are less familiar with computers, [18] although other studies contradict this [12, 19]. Higher education has been associated with the belief that EHRs will improve quality of health care and security [15] but also with a decreased willingness to provide access to personal health information [20, 21]. …”
Section: Introductionmentioning
confidence: 99%